The Impact of Educational Resources Availability on Students Learning Motivation in Primary Schools - Nurmayani; Nursholatiyah Semaya; Deani Salsabila; Nazwa Chelsy Bangun; Rizka Enjeli Situmorang (PT. Anagata Sembagi Education, 2025)
Education is an essential part of human life as it serves as the primary process for developing individual potential from an early age. However, in practice, not all elementary schools have adequate and high-quality educational tools. This study employs a qualitative method with a descriptive approach to describe and analyze the factors influencing students’ learning motivation and the impact of educational tool availability on motivation in elementary schools. The qualitative approach reveals social situations scientifically through accurate descriptions and relevant data analysis based on natural conditions. This research adopts a library study approach by reviewing theories and findings from various scholarly sources. The purpose of this study is to examine the influence of educational tool availability on elementary students’ learning motivation. The findings indicate that the availability of educational tools significantly affects students’ motivation to learn. Concrete, visual, and digital media have been proven to enhance students’ attention, comprehension, and engagement, although their effectiveness largely depends on teacher creativity. Furthermore, disparities in school facilities across regions and differences in family socioeconomic conditions affect the equitable distribution of learning resources. The main obstacles include limited funding, insufficient teacher training, and poor maintenance of educational facilities. Therefore, the provision of adequate tools, the improvement of teacher competence, and equitable educational policies are key to strengthening learning motivation and improving the overall quality of elementary education.